Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 6 - Inverse Circular Functions and Trigonometric Equations - Section 6.4 Equations Involving Inverse Trigonometric Functions - 6.4 Exercises - Page 286: 30



Work Step by Step

Given: $4\pi+4tan^{-1}(x)=\pi$ $4tan^{-1}(x)=-3 \pi$ $tan^{-1}(x)=(-\frac{3 \pi}{4})$ (Divide by 4) $x=tan(-\frac{3 \pi}{4})$ Apply definition of arctangent. $x=1$ Hence, $x=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.